X-ray CT characterization and fracture simulation of ASR damage of glass particles in alkaline solution and mortar. (December 2017) - Guo, Shuaicheng; Dai, Qingli; Sun, Xiao; Xiao, Xianghui
Highlights: Monitor alkali silica reaction (ASR) damage inside glass aggregates with dynamic μm X-ray CT tests. Apply discontinuous displacement method and boundary element method for fracture propagation simulation. Update FRIC 2D codes with plane stress conditions and calibrated SIFs calculation. Favorably compare ASR damage simulation in aggregates with the captured microcracks from μm X-ray CT. Abstract: The alkali-silica reaction (ASR) damage in reactive aggregates affects the long-term durability of the concrete infrastructure. The generated ASR gel can expand by imbibing water from the pore solution and the resulting expansion pressure causes the aggregate fracture. This study aims to simulate the development of ASR damage in glass particles of two types of samples (glass in alkali solution and glass mortars). The dynamic micro X-ray CT technique was conducted to monitor the crack propagation in glass aggregates at different reaction stages (up to 64 h). The Boundary Element Method (BEM) and Displacement Discontinuity Method (DDM) were used to efficiently simulate the crack propagation within irregular glass particles under gel expansion pressures. The aggregate boundaries were built with the BEM elements and the initial cracks were meshed with the DDM elements. The estimated expansion pressure was applied to the initial crack surfaces. The discontinuous displacements and stresses were calculated along the crack path and crack tip. The mixed-mode Stress Intensity Factors (SIFs) were calculated based on plane stress conditions. The maximum circumferential stress criteria were used to simulate the propagation of cracks along a specific angle. The simulation results include the simulated crack path and the combined SIFs changing with the increments. With the estimate expansion pressure, the glass particle damages were simulated within conditions of alkali solution and confined mortar samples. The predicted crack propagation path was compared with the X-ray CT imaging data. The comparison results demonstrate the DDM has the ability to predicting the ASR damage propagation inside aggregates.